2005
DOI: 10.1093/geronb/60.5.s263
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Disability: Recent Evidence From Self-Reported and Performance-Based Disability Measures in a Population-Based Study of Older Adults

Abstract: Racial disparities in disability have not been eliminated, are greater among women, and have their origins earlier in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
135
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 54 publications
16
135
5
Order By: Relevance
“…11,12,35,36 Importantly, the study adds insight into the Hispanic disability experience. Previous cross-sectional national studies report Hispanic versus White differences in prevalent disability.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…11,12,35,36 Importantly, the study adds insight into the Hispanic disability experience. Previous cross-sectional national studies report Hispanic versus White differences in prevalent disability.…”
Section: Discussionmentioning
confidence: 97%
“…These findings show that African American versus White differences in prevalent disability and the development of disability persist into the new century, consonant with earlier national data. 11,12,35,36 Importantly, the study adds insight into the Hispanic disability experience. Previous cross-sectional national studies report Hispanic versus White differences in prevalent disability.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In general, White men had lower levels of lean body mass but higher levels of physical function [4]. Similarly, data from the Chicago Health and Aging Project indicated that Black men and women have lower physical function compared with White men and women [38]. Finally, a recent systematic literature review on the epidemiology of sarcopenia concluded Non-White populations experience a more rapid decline in muscle strength and function compared to White populations [39].…”
Section: Discussionmentioning
confidence: 99%
“…It is also a measure that can be tapped effectively through selfreport (Freedman et al 2011;Maenty et al 2007). Mendes de Leon et al (2005) find it a useful means to capture net changes in mobility from baseline to follow-up. Moreover, Guralnik et al (2000) maintain that lower extremity function demonstrates consistency across studies of diverse populations.…”
Section: Introductionmentioning
confidence: 99%